Efektivitas Kombinasi Pemberian Minyak Ikan Lemuru (Sardinella longiceps) dan Aplikasi Hidroksiapatit terhadap Ekspresi FGF-2 pada Proses Bone Healing - Tiaranita Ramadhani; Rima Parwati Sari; Widyastuti (Denta Journal Kedokteran Gigi, 2016)
Background: Bone healing on defect requiring the cells to form new bone. Fibroblast growth factor -2 belong to one of signaling control that play part in differentiation of fibroblast to osteoblast cell. Hydroxyapatite application on bone healing will aid bone regeneration as structure. Application of Sardinella longiceps oil that contain EPA and DHA as immunodulator could accelerate and optimize inflammatory phase in bone healing. Purpose: The aimed of this study to determine the effectivity of the combination of Sardinella longiceps oil and application of hydroxyapatite on the expression of fibroblast growth factor -2 (FGF-2) in bone healing process. Materials and Methods: The experimental units (male wistar rat, n=20) were devided into two groups, control (K) and treathment (P) groups. Treathment groups were given Sardinella longiceps oil per oral seven days before the surgery to make the defect, and continued for seven days later. Control groups were not given Sardinella longiceps at all. All of the wistar rat were have two defects in their right femur, which is use hydroxyapatite (K+ and P2) and no use hydroxyapatite (K- and P1). Defect was made as big as half diameter of round bur in femur. Rats were sacrificed seven days after surgery, and femur were sliced transversally and performed immunohistochemistry staining with Anti-bFGF Polyclonal antibody (Bioss®). Examination were done under light microscope. Data were analyzed using one-way Anova for FGF-2 expression. Result: Sardinella longiceps oil increased the mean of FGF-2 expression on P2 group : 15,29±5,251, compare to K- : 5,57±2,070 , K+ : 12,14±3,976 and P1 : 8,14±1,676 (P<0.05). Conclusion: The combination of Sardinella longiceps oil and hydroxyapatite application effective the expression of fibroblast growth factor-2 in the process of bone healing.